2008
DOI: 10.1007/s12094-008-0271-0
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal metastases from colon adenocarcinoma

Abstract: Endotracheal metastases (ETM) from non-lung cancer are seldom seen. Their main clinical symptoms are cough, haemoptysis and dyspnoea, although occasionally an incidental finding is made during a bronchoscopy. Breast, colon and kidney adenocarcinoma might be associated with ETM, lung cancer being the most frequent cause. Its finding is associated with advanced disease but survival will depend on the primary origin, patient status and comorbidity. Therefore, treatment should be individual for each patient. In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…There were 64 individual case reports and 96 case series (consisting of more than one case). Of the 96 case series, 17 series contained enough details to extract individual patient data; these 110 patients were analyzed with the individual case reports (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Forty-five case series reported exclusively on tracheal invasion by thyroid cancer (Table S1).…”
Section: Quantity Of Evidencementioning
confidence: 99%
“…There were 64 individual case reports and 96 case series (consisting of more than one case). Of the 96 case series, 17 series contained enough details to extract individual patient data; these 110 patients were analyzed with the individual case reports (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Forty-five case series reported exclusively on tracheal invasion by thyroid cancer (Table S1).…”
Section: Quantity Of Evidencementioning
confidence: 99%
“…Only three cases underwent surgical resection (3)(4)(5), and two patients were treated by laser therapy (3,6). These reports mainly focused on the diagnostic methods of TM and no reports have discussed the optical treatment options, including surgery, of TM of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It could have been missed easily due to its superior position. Galbis Caravajal et al (2) reported a patient with endotracheal metastasis from sigmoid colon cancer who had a missed endotracheal metastasis initially on CT scans, which had been found on a routine bronchoscopic exam.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reported cases of metastases from breast cancer, renal cell carcinoma, melanoma, and colorectal carcinoma (2)(3)(4)(5). Advances in postoperative chemotherapy have increased the survival rate in patients with colorectal carcinoma and have revealed a new population with endobronchial metastases which may arise in the later stages of the disease (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation